Profil Kebugaran Tim Sepakbola Putri Jawa Barat Berdasarkan Denyut Nadi Pada Pekan Olahraga Nasional (PON) XXI Indonesia - Riko, Mia; Muhamad Fahmi; Syafriani, Rini; Juniarsyah, Agung Dwi; Elhaqe, Qintarazany M.; Latief, Gifran Rihla Gifarka; Apriantono, Tommy (Institut Teknologi Bandung, 2024)
An adequate level of physical fitness enables athletes to sustain repeated high-intensity activities, facilitate the recovery process, and maintain optimal physical condition. Regardless of the player's gender (female or male), football players need to achieve a balance in developing physiological and physical capacities. This study aims to analyze the fitness profile of the West Java women's football team that has achieved achievements in the XXI PON Aceh Sumut 2024 based on heart rate data. An observational study was applied involving 14 professional female football players (age: 21.5 ± 2.8 years) and monitoring heart rate conditions (Polar Versity Team Pro) during the match. The average percentage of overall players' heart rate during the match was 90% of the maximum heart rate. The average percentage of heart rate for defenders reached 91%, which differed from midfielders and forwarders during the entire match, reaching 88% and 89% of the maximum heart rate, respectively. The main finding of this study is that the physical fitness condition of professional female football players competing in the competition is declared fit. There was no significant difference in heart rate data from the three positions, indicating that the physical demands of female football players are relatively the same even though they have different roles and positions.